2021
DOI: 10.1177/17446295211022125
|View full text |Cite
|
Sign up to set email alerts
|

The potential for person-centred planning to support the community participation of adults with an intellectual disability

Abstract: Person-centred planning (PCP) puts individuals with an intellectual disability at the centre of service and support planning, identifying how individuals wish to live their lives and what is needed to make that possible. PCP has been identified as having the potential to facilitate improved social inclusion and community participation. A mixed-methods approach combined quantitative analyses with qualitative case studies of individuals with severe-profound intellectual disability to assess the impact of PCP on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Of the two competencies, only timely responsiveness has a net effect on satisfaction with community integration. Although past studies have reported an overall effect of PCP on choice-making (Malette 2002;Neally-Barnes et al 2008;Wigham et al 2008) and social integration (McCausland et al 2022), we were unable to find any large-scale studies that specifically investigate the effects of staff competencies on these outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of the two competencies, only timely responsiveness has a net effect on satisfaction with community integration. Although past studies have reported an overall effect of PCP on choice-making (Malette 2002;Neally-Barnes et al 2008;Wigham et al 2008) and social integration (McCausland et al 2022), we were unable to find any large-scale studies that specifically investigate the effects of staff competencies on these outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…2008) and social integration (McCausland et al . 2022), we were unable to find any large‐scale studies that specifically investigate the effects of staff competencies on these outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…For all domains of QoL, responses include an interaction between objective circumstances and subjective perceptions, evaluations, and feelings about them, and self-reports play an essential role in accurately assessing their QoL. An assessment of QoL without considering self-reports translates into a contradiction, in the sense that decision-making is focused on Person-centered planning [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, Hughes et al (2019) and Morgan (2016) examined the role of using PATH in promoting organisational change, with school staff, and with a children's services department, respectively. McCausland et al (2021), examined the role of PCP in promoting community inclusion in a learning disability service in Dublin.…”
Section: Introductionmentioning
confidence: 99%